2014
DOI: 10.1093/scan/nsu052
|View full text |Cite
|
Sign up to set email alerts
|

Neural underpinnings of superior action prediction abilities in soccer players

Abstract: The ability to form anticipatory representations of ongoing actions is crucial for effective interactions in dynamic environments. In sports, elite athletes exhibit greater ability than novices in predicting other players' actions, mainly based on reading their body kinematics. This superior perceptual ability has been associated with a modulation of visual and motor areas by visual and motor expertise. Here, we investigated the causative role of visual and motor action representations in experts' ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 65 publications
3
55
0
2
Order By: Relevance
“…In keeping with previous rTMS studies showing the relative roles of EBA in processing body form (Candidi et al, 2008;Urgesi, Candidi et al, 2007) and of dPMC in processing body actions (Makris & Urgesi, 2015), we expected that neural activity EBA should inform the aesthetic attribution system of the variations of body size (i.e., being more or less round), while neural activity in dPMC should inform on the variations of implied motion (i.e., displaying more or less 8 implied motion postures) presented in each stimulus. However, the relative contribution of the two areas should vary according to the model's gender.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with previous rTMS studies showing the relative roles of EBA in processing body form (Candidi et al, 2008;Urgesi, Candidi et al, 2007) and of dPMC in processing body actions (Makris & Urgesi, 2015), we expected that neural activity EBA should inform the aesthetic attribution system of the variations of body size (i.e., being more or less round), while neural activity in dPMC should inform on the variations of implied motion (i.e., displaying more or less 8 implied motion postures) presented in each stimulus. However, the relative contribution of the two areas should vary according to the model's gender.…”
Section: Introductionsupporting
confidence: 90%
“…The extension of this shared representation is dependent upon the commonalities of action (i.e., motor repertoire; Calvo-Merino et al, 2005;Aglioti et al, 2008;Makris & Urgesi, 2015) and form (i.e., ethnicity; Müller et al 2011;Avenanti et al, 2010) parameters between the observed and the observer's body. Furthermore, the extent to which the observed dance moves overlap with the observer's motor repertoire (i.e., perceived reproducibility) also affects their aesthetic appreciation (Cross et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TMS was delivered at the very same time point in all conditions, that is at the moment of maximum leg extension of the soccer player after kicking the ball, right before the second step (i.e., stopping or continuing to run). This suggests a motor activation in line with the predicted movement (Kilner et al, 2004;Knoblich & Flach, 2001), finely tuned to early cues in the observed actions (Aglioti et al, 2008;Sartori et al, 2011a;Makris & Urgesi, 2014;Stapel, Hunnius, & Bekkering, 2012). Predicting another person's behavior has immediate implications for one's own action selection system because, depending on the output of action simulation, a suitable action can be selected from a multiplicity of possible alternatives (Bekkering et al, 2009;Sartori et al, 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…As their greater action simulation abilities could have biased the results, individuals with any motor expertise in playing soccer were excluded from the experiment by means of a pre-screening procedure. Athletes, in fact, present superior abilities in predicting and anticipating other players' actions Aglioti et al, 2008;Makris & Urgesi, 2014;Sebanz & Shiffrar, 2009;Tomeo, Cesari, Aglioti, & Urgesi, 2012;Urgesi et al, 2012;Weissensteiner et al, 2008). Notably, also observational practice may contribute to action prediction abilities (Urgesi, Savonitto, Fabbro, & Aglioti, 2012), and soccer is a quite familiar sport.…”
Section: Participantsmentioning
confidence: 99%
“…There was no positive relationship between the amplitude of motor evoked potentials (MEPs) and response accuracy for decisions made when watching congruent (normal penalty kick) actions. Similarly, using repetitive transcranial magnetic stimulation (TMS) to the dorsal premotor cortex (PMd), some of the same group of researchers showed a decrease in prediction accuracy about the outcome of these impossible actions, but again, motor interference did not affect prediction accuracy for the congruent 'real' actions (Makris & Urgesi, 2014). In addition to some potential issues with inferring predictive responses from artificially constructed ''fooling'' actions (see Mann, Dicks, Cañal-Bruland, & van der Kamp, 2013), it is also possible that with this type of dyad task (where a mirrored responder acting as a goalkeeper has to decide kick direction from an approaching soccer player) any general technique which serves to disrupt or activate a specific cortical area would also interfere with the anticipated response (i.e., to move left or right) in addition to any potential simulative processes involved in watching the kickers.…”
Section: Introductionmentioning
confidence: 99%